Studi Penggunaan Packing Plant Pada Distribusi Semen Di Kalimantan Menggunakan Metode Transhipment: Studi Kasus PT Semen Gresik - Ikhyandini Garindia Atristyanti (Jurnal Ekonomi, 2015)
As the largest cement producer in Indonesia, PT Semen Gresik Group has a distribution network spread across the West and the eastern of Indonesia and dominate the national cement market share of about 45%. To support the distribution of velocity throughout the whole country, a strategic step to do is build a packing plant in the area of distribution. The results of the annual analysis, moving closer packing plant to the distribution area can be a solution for efficiency of the transportation costs up to 43% compared to the situation before, and it will be the company's long-term strategic plan. This research will be carried out optimization of the allocation of the cement distribution network in the Kalimantan. Designing a distribution network allocation transhipment model is the development of transport in linear programming models with the help of QM for Windows software. The expected output is the formation of an optimal distribution network with the minimum total cost. To determine the cost efficiency with the packing plant, the optimization model is made will be running four times as much computing. There are four scenarios used without removing the packing plant, with a packing plant in Banjarmasin, a packing plant in Banjarmasin and Pontianak, as well as a packing plant in Banjarmasin, Pontianak and Samarinda. The result of the four scenarios is known that the packing plant can generate cost efficiencies. By including the cost of investment in distribution and transportation costs in mind that in 2020, a third scenario could save Rp 127,229,422,000,-per year than it is without building a packing plant Rp 1,002,443,597,600 to Rp 850,446,425,600.